Consumer behaviour in tourism - Swarbrooke, John.; Horner, Susan, 1956- (Amsterdam : Butterworth-Heinemann, 2007)
Providing an international perspective on consumer behaviour in tourism through the use of examples and case studies, this book looks at consumer behaviour in a number of sectors including: tour operation; tourist destinations; hospitality; visitor attractions; retail travel; and transport.
Previous ed.: 1999.
Includes bibliographical references and index.
Keywords: Consumer behavior; Tourism